Human Mobility in Roman Italy, II: The Slave Population - Scheidel, Walter (The Journal of Roman studies, 2005)
In this paper, I seek to delineate the build-up of the Italian slave population. My parametric model revolves around two variables: the probable number of slaves in Roman Italy, and the demographic structure of the servile population. I critique existing estimates of slave totals and propose a new ‘bottom-up’ approach; discuss the probable sex ratio, mortality regime and family structure of the Italian slaves; and advance a new estimate of the overall volume of slave transfers. I argue that the total number of slaves in Roman Italy did not exceed one-and-a-half million, and that this population had been created by the influx of between two and four million slaves during the last two centuries B.C.